Sealant for liquid crystal display devices
The sealant for liquid crystal display devices, comprising a curable resin with a specific compound, photopolymerization initiator, and fillers, addresses the issue of peeling after light curing by ensuring excellent adhesion, moisture permeability, and adjustable bond strength, even on large substrates.
Patent Information
- Application Number
- JP2024504240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-01-16
- Filing Date
- 2024-01-12
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2044-01-12
AI Technical Summary
Existing sealants for liquid crystal display devices face challenges with peeling after light curing, especially when applied to large substrates, due to inadequate adhesion to alignment films and moisture permeability.
A sealant composition containing a curable resin with a specific compound represented by formula (1), a photopolymerization initiator, and optional organic and inorganic fillers, which provides excellent adhesion to alignment films, moisture permeability, and adjustable low-speed compression shear bond strength to prevent peeling.
The sealant achieves excellent adhesion to alignment films, maintains moisture permeability, and effectively suppresses peeling after light curing, even on large substrates, by optimizing the compression shear bond strength and storage elastic modulus.
Smart Images

Figure 0007649420000001 
Figure 0007649420000002 
Figure 0007649420000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant for liquid crystal display elements that has excellent adhesion to alignment films and moisture permeability prevention properties, and that can suppress peeling after photocuring even when applied to a large substrate. [Background technology]
[0002] In recent years, a liquid crystal dropping method, known as a dropping method, using a light-and-heat-curing sealant containing a curable resin, a photopolymerization initiator, and a heat curing agent, as disclosed in Patent Documents 1 and 2, has been used as a manufacturing method for liquid crystal display elements from the viewpoints of shortening takt time and optimizing the amount of liquid crystal used.
[0003] In recent years, as a manufacturing method for liquid crystal display elements such as liquid crystal display cells, from the viewpoint of shortening takt time and optimizing the amount of liquid crystal used, a method called a dropping method using a curable resin composition as a sealant, as disclosed in Patent Documents 1 and 2, has been used. In the drip method, first, a sealant is applied to one of two substrates with electrodes, forming a frame-shaped seal pattern. Next, while the sealant is still in an uncured state, tiny droplets of liquid crystal are dripped into the seal frame of the substrate, and the other substrate is placed on top of it in a vacuum, and the sealant is cured by light irradiation or heating to create a liquid crystal display element. Currently, this drip method is the mainstream method for manufacturing liquid crystal display elements. With such narrow frame designs, the sealant is often applied to an alignment film such as polyimide. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-133794 A [Patent Document 2] WO 02 / 092718 Summary of the Invention [Problem to be solved by the invention]
[0005] Typically, liquid crystal display elements are manufactured by forming a plurality of cells on a mother glass at once, and then cutting each of them. In recent years, mother glass and displays have become larger, and peeling of the substrate is more likely to occur during the manufacturing process of liquid crystal display elements. Conventionally, from the viewpoint of adhesiveness and moisture permeability prevention, (meth)acrylic compounds and the like have been used as a curable resin to be mixed into a sealant, and this is photocured, but peeling of the substrate sometimes occurred due to vibrations during transportation, especially after the photocuring process. An object of the present invention is to provide a sealant for liquid crystal display elements which has excellent adhesion to an alignment film and moisture permeability prevention properties, and which can suppress peeling after photocuring even when applied to a large substrate. [Means for solving the problem]
[0006] Disclosure 1 relates to a sealant for liquid crystal display elements, which contains a curable resin and a photopolymerization initiator, and the curable resin contains a compound represented by the following formula (1), and the sealant is irradiated with ultraviolet light having a wavelength of 365 nm at a rate of 3000 mJ / cm 2 The cured product of the above sealant for liquid crystal display elements obtained by irradiating the liquid crystal display element has a thickness of 5.0 μm, and the compressive shear adhesive strength to polyimide measured at 25°C and a shear rate of 1 mm / sec according to JIS K 6852 is 15 kgf / cm 2 The above is the sealant for liquid crystal display elements. The present disclosure 2 is the sealant for liquid crystal display elements according to the present disclosure 1, further comprising an organic filler, the content of the organic filler being 5 parts by mass or more relative to 100 parts by mass of the curable resin. In the present disclosure 3, the ratio of the number of epoxy groups in one molecule of the compound contained in the curable resin to the total number of epoxy groups and (meth)acryloyl groups in the compound is defined as P E When the above-mentioned curable resin as a whole is E The sealant for liquid crystal display elements according to Disclosure 1 or 2 has an epoxy functional group ratio, expressed as a mass average value, of 30% or more. The present disclosure 4 is the sealant for liquid crystal display elements according to the present disclosure 1, 2 or 3, further comprising an inorganic filler, the content of the inorganic filler being 5 parts by mass or more and 30 parts by mass or less relative to 100 parts by mass of the curable resin. Disclosure 5 provides a 3000mJ / cm2 ultraviolet ray with a wavelength of 365 nm. 2 After irradiation, the product is heated at 120°C for 1 hour to obtain a cured product with a thickness of 300 μm. The moisture permeability of the product measured in accordance with JIS Z 0208 at 80°C and 90% RH is 75 g / m 2 The sealant for a liquid crystal display element according to Disclosure 1, 2, 3 or 4, wherein the sealant has a life of 24 hours or less. Disclosure 6 provides 3000 mJ / cm2 ultraviolet light with a wavelength of 365 nm. 2 The sealant for liquid crystal display elements according to Disclosure 1, 2, 3, 4 or 5, wherein the storage modulus at 25° C. of the cured product obtained by irradiation is 3.5 GPa or less.
[0007] [ka]
[0008] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a group represented by the following formula (2-1), (2-2), or (2-3), and R 3 represents a methylene group, a methylmethylene group, a dimethylmethylene group, or a sulfonyl group; X represents a lactone ring-open structure; and n is 1 or more and 5 or less.
[0009] [ka]
[0010] In formulas (2-1) to (2-3), * represents a bonding position; in formula (2-2), a is an integer of 1 or more and 8 or less; in formula (2-3), b is an integer of 1 or more and 8 or less; c is an integer of 1 or more and 3 or less; and d is an integer of 1 or more and 8 or less. The present invention will be described in detail below.
[0011] The present inventors have investigated adjusting the peel adhesion strength of the sealant after photocuring by using a partially (meth)acrylic compound having a specific flexible backbone in order to suppress peeling after photocuring while obtaining excellent adhesion and moisture permeability prevention properties to the alignment film. However, even if the peel adhesion strength is adjusted, reproducibility of the effect of suppressing peeling after photocuring cannot be obtained. Therefore, the present inventors have investigated adjusting the low-speed compressive shear adhesive strength of the sealant after photocuring at a shear rate of 1 mm / sec to a specific value or more. As a result, they have found that it is possible to obtain a sealant for liquid crystal display elements that has excellent adhesion and moisture permeability prevention properties to the alignment film and can suppress peeling after photocuring even when applied to a large substrate, and have completed the present invention.
[0012] The sealant for liquid crystal display devices of the present invention is irradiated with ultraviolet light having a wavelength of 365 nm at a rate of 3000 mJ / cm 2 The cured product of the above-mentioned sealant for liquid crystal display elements obtained by irradiating the liquid crystal display element with light has a thickness of 5.0 μm, and the compressive shear adhesive strength to a glass substrate measured at 25° C. and a shear rate of 1 mm / sec in accordance with JIS K 6852 (hereinafter also referred to as "low-speed compressive shear adhesive strength after photocuring") has a lower limit of 15 kgf / cm. 2 The low-speed compressive shear adhesive strength after photocuring is 15 kgf / cm 2 Due to the above, the sealant for liquid crystal display elements of the present invention can suppress peeling after photocuring. The preferable lower limit of the low-speed compressive shear adhesive strength after photocuring is 20 kgf / cm 2 , and a more preferable lower limit is 25kgf / cm 2 It is. Although there is no particular upper limit to the low-speed compressive shear adhesive strength after photocuring, the practical upper limit is 100 kgf / cm 2 It is. The low-speed compressive shear adhesive strength after photocuring can be measured by the following method. That is, first, a polyimide solution is applied to an ITO substrate 45 mm long, 25 mm wide, and 0.7 mm thick in a thickness of about 100 nm, and two substrates (polyimide substrates) are prepared by processing the substrate, and a sealant is applied to one of the substrates in dots so that the diameter when bonded is 3 mm. The other polyimide substrate is placed on top of the polyimide substrate with the sealant dotted on it, shifted 10 mm in the longitudinal direction, and the sealant is placed between them. After that, a metal halide lamp or the like is used to apply ultraviolet light with a wavelength of 365 nm at 3000 mJ / cm. 2 The sealant is cured by irradiation, and a test piece having a thickness of 5.0 μm is obtained. The low-speed compressive shear adhesive strength of the test piece obtained after photocuring can be measured at 25°C and a shear rate of 1 mm / sec in accordance with JIS K 6852.
[0013] The sealant for liquid crystal display devices of the present invention is irradiated with ultraviolet light having a wavelength of 365 nm at a rate of 3000 mJ / cm 2 After irradiation, the cured product is heated at 120°C for 1 hour to obtain a thickness of 300 μm. The preferred upper limit of the moisture permeability in an environment of 80°C and 90% RH, as measured in accordance with JIS Z 0208, is 75 g / m 2 24hr. The moisture permeability is 75g / m 2 By setting the moisture permeability to 24 hours or less, the obtained liquid crystal display device has better reliability. 2 -24hr. Although there is no particular preferred lower limit for the moisture permeability, the substantial lower limit is 35 g / m 2 -24hr.
[0014] The sealant for liquid crystal display devices of the present invention is irradiated with ultraviolet light having a wavelength of 365 nm at a rate of 3000 mJ / cm 2 The preferred upper limit of the storage modulus at 25°C of the cured product obtained by irradiation (hereinafter also referred to as "storage modulus after photocuring") is 3.5 GPa. When the storage modulus after photocuring is 3.5 GPa or less, the sealant for liquid crystal display elements of the present invention has a superior effect of suppressing peeling after photocuring. The more preferred upper limit of the storage modulus after photocuring is 3.0 GPa. From the viewpoint of adhesiveness when the adherend is bonded, the lower limit of the storage modulus after photocuring is preferably 0.1 GPa, and more preferably 1.0 GPa. The storage modulus can be measured using a dynamic viscoelasticity measuring device (e.g., "DVA-200" manufactured by IT Measurement & Control Co., Ltd.) under the conditions of a tensile mode, a test piece width of 5 mm, a thickness of 0.35 mm, a grip width of 25 mm, a heating rate of 10°C / min, and a frequency of 5 Hz.
[0015] The low-speed compressive shear adhesive strength after photocuring, the moisture permeability, and the storage modulus after photocuring can be set within the above-mentioned ranges by selecting the types and adjusting the content ratios of the curable resin, photopolymerization initiator, and other components such as an organic filler and an inorganic filler, which will be described later.
[0016] The sealing agent for a liquid crystal display element of the present invention contains a curable resin. The curable resin contains a compound represented by the formula (1). By containing the compound represented by the formula (1), the sealant for liquid crystal display elements of the present invention has excellent adhesion to an alignment film and moisture permeability prevention properties, and it is easy to set the low-speed compressive shear adhesive strength after photocuring and the storage modulus after photocuring in the above-mentioned ranges.
[0017] In the above formula (1), R 2 represents a group represented by the above formula (2-1), (2-2), or (2-3). Among these, from the viewpoint of the adhesiveness of the resulting sealant for liquid crystal display elements and the flexibility of the cured product, the above R 2 is preferably a group represented by the above formula (2-2), and more preferably a group in which a in the above formula (2-2) is 2 (ethylene group). In the above formula (2-1) and formula (2-3), among the bonding positions marked with *, the bonding position on the methylene group side is the bonding position with the (meth)acryloyloxy group in the above formula (1). In this specification, the term "(meth)acryloyl" means acryloyl or methacryloyl.
[0018] In the above formula (1), R 3 represents a methylene group, a methylmethylene group, a dimethylmethylene group, or a sulfonyl group. 3 is preferably a methylene group, a methylmethylene group, or a dimethylmethylene group.
[0019] In the above formula (1), X represents a ring-opened lactone structure. Examples of the lactone include γ-undecalactone, ε-caprolactone, γ-decalactone, σ-dodecalactone, γ-nonanolactone, γ-heptanolactone, γ-valerolactone, σ-valerolactone, β-butyrolactone, γ-butyrolactone, β-propiolactone, σ-hexanolactone, 7-butyl-2-oxepanone, etc. Among these, those having a linear portion of the main skeleton with 5 or more and 7 or less carbon atoms when ring-opened are preferred.
[0020] Examples of methods for producing the compound represented by the above formula (1) include the following methods. That is, first, the hydroxyl group and the above R 2 and a lactone by heating and stirring in the presence of a polymerization inhibitor, and then the above-mentioned phthalic acid or phthalic anhydride is added and reacted by heating and stirring, etc. Next, an epoxy compound having a bisphenol skeleton, such as bisphenol A diglycidyl ether, is added to the resulting reaction product and heated and stirred, etc., to react some of the epoxy groups of the epoxy compound having a bisphenol skeleton. In this specification, the term "(meth)acrylic" means acrylic or methacrylic.
[0021] The curable resin preferably contains a curable resin other than the compound represented by formula (1) for the purpose of adjusting the low-speed compressive shear adhesive strength after photocuring, the moisture permeability, and the storage modulus after photocuring, or for the purpose of improving low liquid crystal contamination properties. When the other curable resin is contained, the content of the compound represented by the formula (1) in 100 parts by mass of the curable resin is preferably 10 parts by mass at the lower limit and 70 parts by mass at the upper limit. By having the content of the compound represented by the formula (1) in this range, it becomes easier to set the low-speed compressive shear adhesive strength after photocuring, the moisture permeability, and the storage modulus after photocuring in the above-mentioned ranges. The more preferred lower limit of the content of the compound represented by the formula (1) is 15 parts by mass, and the more preferred upper limit is 50 parts by mass.
[0022] Examples of the other curable resins include epoxy compounds and (meth)acrylic compounds.
[0023] Examples of the epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber modified type epoxy compounds, and glycidyl ester compounds.
[0024] Among the above bisphenol A type epoxy compounds, commercially available ones include, for example, jER828EL, jER1004 (both manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-850CRP (manufactured by DIC Corporation), and the like. Among the above bisphenol F type epoxy compounds, commercially available ones include, for example, jER806 and jER4004 (both manufactured by Mitsubishi Chemical Corporation). Among the above bisphenol S type epoxy compounds, commercially available ones include, for example, EPICLON EXA1514 (manufactured by DIC Corporation). Among the above 2,2'-diallylbisphenol A type epoxy compounds, a commercially available example is RE-810NM (manufactured by Nippon Kayaku Co., Ltd.). Among the above hydrogenated bisphenol type epoxy compounds, commercially available ones include, for example, EPICLON EXA7015 (manufactured by DIC Corporation). Among the above propylene oxide-added bisphenol A type epoxy compounds, commercially available ones include, for example, EP-4000S (manufactured by ADEKA Corporation). Among the above resorcinol type epoxy compounds, a commercially available example is EX-201 (manufactured by Nagase ChemteX Corporation). Among the biphenyl type epoxy compounds, examples of commercially available compounds include jER YX-4000H (manufactured by Mitsubishi Chemical Corporation). Among the above sulfide type epoxy compounds, a commercially available example is YSLV-50TE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the diphenyl ether type epoxy compounds, a commercially available example is YSLV-80DE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above dicyclopentadiene type epoxy compounds, commercially available ones include, for example, EP-4088S (manufactured by ADEKA Corporation). Among the above naphthalene type epoxy compounds, commercially available ones include, for example, EPICLON HP4032, EPICLON EXA-4700 (both manufactured by DIC Corporation), and the like. Among the above phenol novolac type epoxy compounds, a commercially available example is EPICLON N-770 (manufactured by DIC Corporation). Among the above ortho-cresol novolac type epoxy compounds, a commercially available example is EPICLON N-670-EXP-S (manufactured by DIC Corporation). Among the above dicyclopentadiene novolac type epoxy compounds, a commercially available example is EPICLON HP7200 (manufactured by DIC Corporation). Among the biphenyl novolac type epoxy compounds, a commercially available example is NC-3000P (manufactured by Nippon Kayaku Co., Ltd.). Among the above naphthalenephenol novolac type epoxy compounds, a commercially available example is ESN-165S (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above glycidylamine type epoxy compounds, commercially available ones include, for example, jER630 (manufactured by Mitsubishi Chemical Corporation), EPICLON 430 (manufactured by DIC Corporation), TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, Inc.), and the like. Commercially available examples of the alkyl polyol type epoxy compounds include ZX-1542 (manufactured by Nippon Steel Chemical & Materials Co., Ltd.), EPICLON 726 (manufactured by DIC Corporation), Epolite 80MFA (manufactured by Kyoeisha Chemical Co., Ltd.), and Denacol EX-611 (manufactured by Nagase ChemteX Corporation). Among the above rubber-modified epoxy compounds, commercially available ones include, for example, YR-450, YR-207 (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), Epolead PB (manufactured by Daicel Corporation), and the like. Among the above glycidyl ester compounds, commercially available ones include, for example, Denacol EX-147 (manufactured by Nagase Chemtex Corporation). Other commercially available epoxy compounds include, for example, YDC-1312, YSLV-80XY, YSLV-90CR (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), XAC4151 (manufactured by Asahi Kasei Corporation), jER1031, jER1032 (all manufactured by Mitsubishi Chemical Corporation), EXA-7120 (manufactured by DIC Corporation), and TEPIC (manufactured by Nissan Chemical Industries, Ltd.).
[0025] The curable resin may contain a compound having an epoxy group and a (meth)acryloyl group in one molecule other than the compound represented by formula (1) as the other curable resin. Examples of such compounds include partially (meth)acrylic modified epoxy compounds obtained by reacting a part of the epoxy groups of an epoxy compound having two or more epoxy groups in one molecule with (meth)acrylic acid.
[0026] Examples of the (meth)acrylic compound include (meth)acrylic acid ester compounds, epoxy (meth)acrylates, and urethane (meth)acrylates. Among these, epoxy (meth)acrylates are preferred. In addition, the (meth)acrylic compound is preferably one having two or more (meth)acryloyl groups in one molecule from the viewpoint of reactivity. In this specification, the term "(meth)acrylate" means acrylate or methacrylate, and the term "epoxy (meth)acrylate" means a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.
[0027] Examples of the monofunctional (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and isoctyl (meth)acrylate. Somyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2 -Butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropionate Examples of the acrylates include 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, and glycidyl (meth)acrylate.
[0028] Examples of the bifunctional (meth)acrylic acid ester compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and the like. Examples of the di(meth)acrylate include butyl di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, and polybutadiene diol di(meth)acrylate.
[0029] In addition, examples of the (meth)acrylic acid ester compounds having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0030] The epoxy (meth)acrylate may be, for example, one obtained by reacting an epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method. The epoxy compound that is the raw material for the epoxy (meth)acrylate may be the epoxy compound listed above as the other curable resin.
[0031] Among the above epoxy (meth)acrylates, commercially available ones include, for example, epoxy (meth)acrylate manufactured by Daicel-Allnex Corporation, epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd., and epoxy (meth)acrylate manufactured by Nagase ChemteX Corporation. Examples of the epoxy (meth)acrylates manufactured by Daicel-Allnex include EBECRYL860, EBECRYL3200, EBECRYL3201, EBECRYL3412, EBECRYL3600, EBECRYL3700, EBECRYL3701, EBECRYL3702, EBECRYL3703, EBECRYL3708, EBECRYL3800, EBECRYL6040, and EBECRYL RDX63182. Examples of the epoxy (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include EA-1010, EA-1020, EA-5323, EA-5520, EA-CHD, and EMA-1020. Examples of the epoxy (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include Epoxy Ester M-600A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 1600A, Epoxy Ester 3000M, Epoxy Ester 3000A, Epoxy Ester 200EA, and Epoxy Ester 400EA. Examples of the epoxy (meth)acrylates manufactured by Nagase ChemteX Corporation include Denacol Acrylate DA-141, Denacol Acrylate DA-314, and Denacol Acrylate DA-911.
[0032] The urethane (meth)acrylate can be obtained, for example, by reacting a polyfunctional isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.
[0033] Examples of the polyfunctional isocyanate compound include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.
[0034] As the polyfunctional isocyanate compound, a chain-extended polyfunctional isocyanate compound obtained by reacting a polyol with an excess of the polyfunctional isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0035] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, mono(meth)acrylates or di(meth)acrylates of trihydric alcohols, and epoxy (meth)acrylates. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin. The epoxy (meth)acrylate may, for example, be bisphenol A type epoxy acrylate.
[0036] Among the above urethane (meth)acrylates, commercially available ones include, for example, urethane (meth)acrylate manufactured by Toagosei Co., Ltd., urethane (meth)acrylate manufactured by Daicel-Allnex Corporation, urethane (meth)acrylate manufactured by Negami Chemical Industries Co., Ltd., urethane (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., and urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. Examples of the urethane (meth)acrylates manufactured by Toagosei Co., Ltd. include M-1100, M-1200, M-1210, and M-1600. Examples of the urethane (meth)acrylates manufactured by Daicel-Allnex include EBECRYL210, EBECRYL220, EBECRYL230, EBECRYL270, EBECRYL1290, EBECRYL2220, EBECRYL4827, EBECRYL4842, EBECRYL4858, EBECRYL5129, EBECRYL6700, EBECRYL8402, EBECRYL8803, EBECRYL8804, EBECRYL8807, EBECRYL9260, and the like. Examples of the urethane (meth)acrylates manufactured by Negami Chemical Industrial Co., Ltd. include Art Resin UN-330, Art Resin SH-500B, Art Resin UN-1200TPK, Art Resin UN-1255, Art Resin UN-3320HB, Art Resin UN-7100, Art Resin UN-9000A, Art Resin UN-9000H, etc. Examples of the urethane (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include U-2HA, U-2PHA, U-3HA, U-4HA, U-6H, U-6HA, U-6LPA, U-10H, U-15HA, U-108, U-108A, U-122A, U-122P, U-324A, U-340A, U-340P, U-1084A, U-2061BA, UA-340P, UA-4000, UA-4100, UA-4200, UA-4400, UA-5201P, UA-7100, UA-7200, and UA-W2A. Examples of the urethane (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include AH-600, AI-600, AT-600, UA-101I, UA-101T, UA-306H, UA-306I, and UA-306T.
[0037] The ratio of the number of epoxy groups in one molecule of the compound contained in the curable resin to the total number of epoxy groups and (meth)acryloyl groups in one molecule of the compound is defined as P E When the above-mentioned curable resin as a whole is EThe preferred lower limit of the epoxy functional group ratio expressed as the mass average value of is 30%. When the epoxy functional group ratio is 30% or more, it becomes easier to set the low-speed compressive shear adhesive strength after photocuring and the storage modulus after photocuring within the above-mentioned ranges. The more preferred lower limit of the epoxy functional group ratio is 35%. From the viewpoint of low liquid crystal contamination, the upper limit of the epoxy functional group ratio is preferably 50%, and more preferably 45%.
[0038] The sealing agent for liquid crystal display elements of the present invention contains a photopolymerization initiator. Examples of the photopolymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds. Specific examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)- ... -morpholinopropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2-(acetoxyimino)-1-(4-(4-(2-hydroxyethoxy)phenylthio)phenyl)propan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4-dimethylthioxanthen-9-one, and the like.
[0039] The content of the photopolymerization initiator is preferably 0.01 parts by mass at the lower limit and 10 parts by mass at the upper limit with respect to 100 parts by mass of the curable resin. By setting the content of the photopolymerization initiator within this range, the resulting sealant for liquid crystal display elements has better storage stability and photocurability. The more preferred lower limit of the content of the photopolymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0040] The sealing agent for a liquid crystal display element of the present invention may contain a thermal polymerization initiator. Examples of the thermal polymerization initiator include those composed of an azo compound, an organic peroxide, etc. Among them, a polymeric azo initiator composed of a polymeric azo compound is preferred. The thermal polymerization initiators may be used alone or in combination of two or more kinds. In this specification, the term "polymeric azo compound" refers to a compound that has an azo group, generates radicals by heat, and has a number average molecular weight of 300 or more.
[0041] The number average molecular weight of the polymer azo compound is preferably 1000 at the lower limit and 300,000 at the upper limit. The number average molecular weight of the polymer azo compound is within this range, so that the polymer azo compound can be easily mixed with the curable resin while suppressing liquid crystal contamination. The number average molecular weight of the polymer azo compound is more preferably 5000 at the lower limit and 100,000 at the upper limit, and even more preferably 10,000 at the lower limit and 90,000 at the upper limit.
[0042] Examples of the polymeric azo compound include those having a structure in which a plurality of units such as polyalkylene oxide and polydimethylsiloxane are bonded via azo groups. As the polymeric azo compound having a structure in which a plurality of units such as polyalkylene oxide are bonded via the azo group, those having a polyethylene oxide structure are preferred. Specific examples of the polymeric azo compound include a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polyalkylene glycol, and a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polydimethylsiloxane having a terminal amino group. Among the above polymeric azo compounds, commercially available ones include, for example, VPE-0201, VPE-0401, VPE-0601, VPS-0501, and VPS-1001 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). Examples of non-polymeric azo compounds include V-65 and V-501 (both manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0043] Examples of the organic peroxide include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, peroxy esters, diacyl peroxides, and peroxydicarbonates.
[0044] The content of the thermal polymerization initiator is preferably 0.05 parts by mass at the lower limit and 10 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. When the content of the thermal polymerization initiator is 0.05 parts by mass or more, the sealant for liquid crystal display elements of the present invention has better thermosetting properties. When the content of the thermal polymerization initiator is 10 parts by mass or less, the sealant for liquid crystal display elements of the present invention has better low liquid crystal contamination properties and storage stability. The more preferred lower limit of the content of the thermal polymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0045] The sealing agent for liquid crystal display elements of the present invention preferably contains a heat curing agent. Examples of the heat curing agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyhydric phenol compounds, acid anhydrides, etc. Among these, organic acid hydrazides are preferably used.
[0046] Examples of the organic acid hydrazide include sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide. Among the above organic acid hydrazides, commercially available ones include, for example, organic acid hydrazides manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Ltd., and organic acid hydrazides manufactured by Nippon Finechem Co., Ltd. Examples of the organic acid hydrazides available from Otsuka Chemical Co., Ltd. include SDH and ADH. Examples of the organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Inc. include Amicure VDH, Amicure VDH-J, Amicure UDH, and Amicure UDH-J. The organic acid hydrazide manufactured by Japan Finechem Co., Ltd. is, for example, MDH.
[0047] The content of the heat curing agent is preferably 1 part by mass at the lower limit and 50 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. By setting the content of the heat curing agent within this range, the resulting sealant for liquid crystal display elements has excellent heat curing properties while maintaining storage stability and coatability. The more preferred upper limit of the content of the heat curing agent is 30 parts by mass.
[0048] The sealant for liquid crystal display elements of the present invention preferably contains an organic filler. By containing the organic filler, it becomes easier to set the low-speed compressive shear adhesive strength after photocuring and the storage modulus after photocuring within the above-mentioned ranges.
[0049] Examples of the organic filler include polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, and (meth)acrylic polymer fine particles. The organic filler may have a core-shell structure. Among them, (meth)acrylic polymer fine particles having a core-shell structure are preferred.
[0050] The organic filler has a preferred lower limit of 0.1 μm and a preferred upper limit of 0.8 μm. By setting the organic filler's average particle size in this range, it becomes easier to set the low-speed compression shear adhesive strength after photocuring and the storage modulus after photocuring in the above-mentioned ranges. The organic filler's more preferred upper limit of the average particle size is 0.5 μm. The average particle size of the organic filler can be measured by dispersing the organic filler in a solvent (water, organic solvent, etc.) using a particle size distribution measuring device. Examples of the particle size distribution measuring device include NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0051] The content of the organic filler is preferably 5 parts by mass relative to 100 parts by mass of the curable resin. By making the content of the organic filler 5 parts by mass or more, it becomes easier to make the low-speed compression shear adhesive strength after photocuring and the storage modulus after photocuring fall within the above-mentioned range. The more preferable lower limit of the content of the organic filler is 10 parts by mass. From the viewpoint of coatability and the like, the upper limit of the content of the organic filler is preferably 40 parts by mass, and more preferably 30 parts by mass.
[0052] The sealant for liquid crystal display elements of the present invention preferably contains the inorganic filler for the purposes of improving moisture permeability prevention, increasing viscosity, improving adhesion due to a stress dispersion effect, improving the linear expansion coefficient, etc. However, when the inorganic filler is contained in a large amount, it becomes difficult to set the low-speed compressive shear adhesive strength after photocuring and the storage modulus after photocuring to be within the above-mentioned ranges.
[0053] Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate.
[0054] The content of the inorganic filler is preferably 5 parts by mass at the lower limit and 30 parts by mass at the upper limit relative to 100 parts by mass of the curable resin. When the content of the inorganic filler is 5 parts by mass or more, the effect of improving moisture permeability prevention is more excellent. When the content of the inorganic filler is 30 parts by mass or less, it is easier to set the low-speed compression shear adhesive strength after photocuring and the storage modulus after photocuring to the above-mentioned range. A more preferable lower limit of the content of the inorganic filler is 10 parts by mass, and a more preferable upper limit is 25 parts by mass.
[0055] The sealant for liquid crystal display elements of the present invention preferably contains a silane coupling agent. The silane coupling agent mainly serves as an adhesion aid for providing good adhesion between the sealant for liquid crystal display elements and a substrate or the like. As the silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, etc. are suitably used.
[0056] The content of the silane coupling agent in 100 parts by mass of the sealant for liquid crystal display element of the present invention is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit. By the content of the silane coupling agent being within this range, the effect of improving adhesion while suppressing the occurrence of liquid crystal contamination is excellent. The content of the silane coupling agent is more preferably 0.3 parts by mass at the lower limit and 5 parts by mass at the upper limit.
[0057] The sealant for a liquid crystal display element of the present invention may contain a light-shielding agent. By containing the light-shielding agent, the sealant for a liquid crystal display element of the present invention can be suitably used as a light-shielding sealant.
[0058] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, resin-coated carbon black, etc. Among these, titanium black is preferable.
[0059] The titanium black is a substance that has a higher transmittance for light near the ultraviolet region, particularly light with a wavelength of 370 nm to 450 nm, compared to the average transmittance for light with a wavelength of 300 nm to 800 nm. That is, the titanium black is a light-shielding agent that imparts light-shielding properties to the sealant for liquid crystal display elements of the present invention by sufficiently blocking light with wavelengths in the visible light region, while allowing light with wavelengths near the ultraviolet region to pass through. Therefore, by using, as the photopolymerization initiator, one that can initiate a reaction with light of a wavelength (370 nm to 450 nm) at which the transmittance of the titanium black is high, the photocuring property of the sealant for liquid crystal display elements of the present invention can be further increased. In addition, the light-shielding agent contained in the sealant for liquid crystal display elements of the present invention is preferably a substance with high insulating properties, and titanium black is also suitable as a light-shielding agent with high insulating properties. The titanium black preferably has an optical density (OD value) per 1 μm of 3 or more, more preferably 4 or more. The higher the light blocking ability of the titanium black, the better. There is no particular upper limit to the OD value of the titanium black, but it is usually 5 or less.
[0060] Although the titanium black exhibits sufficient effects even when not surface-treated, it is also possible to use titanium black whose surface has been treated with an organic component such as a coupling agent, or titanium black whose surface has been coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc. Among these, titanium black treated with an organic component is preferred in that it can further improve insulation properties. Furthermore, a liquid crystal display element manufactured using the sealing agent for liquid crystal display elements of the present invention, which contains the above-mentioned titanium black as a light-blocking agent, has sufficient light-blocking properties, so that it is possible to realize a liquid crystal display element that has no light leakage, high contrast, and excellent image display quality.
[0061] Among the titanium blacks mentioned above, commercially available titanium blacks include, for example, titanium black manufactured by Mitsubishi Materials Corporation and titanium black manufactured by Ako Kasei Co., Ltd. Examples of the titanium black manufactured by Mitsubishi Materials Corporation include 12S, 13M, 13M-C, 13R-N, and 14M-C. An example of the titanium black manufactured by Ako Kasei Co., Ltd. is Tilac D.
[0062] The preferred lower limit of the specific surface area of the titanium black is 13 m 2 / g, the preferred upper limit is 30m 2 / g, and a more preferable lower limit is 15m 2 / g, with a more preferable upper limit of 25m 2 / g. The volume resistivity of the titanium black preferably has a lower limit of 0.5 Ω·cm and a higher limit of 3 Ω·cm, more preferably a lower limit of 1 Ω·cm and a more preferably upper limit of 2.5 Ω·cm.
[0063] The primary particle diameter of the light-shielding agent is not particularly limited as long as it is equal to or smaller than the distance between the substrates of the liquid crystal display element, but the preferred lower limit is 1 nm, and the preferred upper limit is 5000 nm. By setting the primary particle diameter of the light-shielding agent within this range, the obtained sealant for liquid crystal display elements can have excellent light-shielding properties without deteriorating the coatability, etc. of the sealant. The more preferred lower limit of the primary particle diameter of the light-shielding agent is 5 nm, the more preferred upper limit is 200 nm, the even more preferred lower limit is 10 nm, and the even more preferred upper limit is 100 nm. The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, organic solvent, etc.) using NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0064] The preferred lower limit of the content of the light-shielding agent in 100 parts by mass of the sealant for liquid crystal display elements of the present invention is 5 parts by mass, and the preferred upper limit is 80 parts by mass. By having the content of the light-shielding agent in this range, the adhesiveness, post-curing strength, and drawability of the resulting sealant for liquid crystal display elements are not reduced, and the effect of improving the light-shielding property can be more effectively exhibited. The more preferred lower limit of the content of the light-shielding agent is 10 parts by mass, the more preferred upper limit is 70 parts by mass, the even more preferred lower limit is 30 parts by mass, and the even more preferred upper limit is 60 parts by mass.
[0065] The sealing material for liquid crystal display elements of the present invention may further contain additives such as a stress relaxation agent, a reactive diluent, a curing accelerator, an antifoaming agent, a leveling agent, and a polymerization inhibitor, if necessary.
[0066] The method for producing the sealing agent for liquid crystal display elements of the present invention may, for example, be a method in which a curable resin, a photopolymerization initiator, and other components such as an organic filler or an inorganic filler are mixed using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.
[0067] Moreover, by blending conductive fine particles with the sealing agent for liquid crystal display elements of the present invention, a vertically conductive material can be produced. The conductive fine particles may be metal balls, fine resin particles having a conductive metal layer formed on the surface thereof, etc. Among them, fine resin particles having a conductive metal layer formed on the surface thereof are preferable because the excellent elasticity of the fine resin particles allows conductive connection without damaging a transparent substrate, etc.
[0068] As a method for producing a liquid crystal display element using the sealant for a liquid crystal display element of the present invention, a liquid crystal dropping method is suitably used, and specifically, for example, a method having the following steps can be mentioned. First, a process is performed in which the sealant for liquid crystal display elements of the present invention is applied by screen printing, dispenser application, or the like onto the alignment film of one of two transparent substrates having electrodes such as ITO thin films and an alignment film, thereby forming a frame-shaped seal pattern. Next, a process is performed in which minute droplets of liquid crystal are dropwise applied onto the entire surface within the frame of the seal pattern, and the other transparent substrate is superimposed under vacuum. After that, a liquid crystal display element can be obtained by a process of irradiating the seal pattern portion with light such as ultraviolet light to provisionally cure the sealant (photocuring process), and a process of heating the provisionally cured sealant to fully cure it (thermal curing process). Effect of the Invention
[0069] According to the present invention, it is possible to provide a sealant for liquid crystal display elements which has excellent adhesion to an alignment film and moisture-proofing properties, and which can suppress peeling after photocuring even when applied to a large substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0071] (Preparation of hardening resin A) 116 parts by mass of 2-hydroxyethyl acrylate, 114 parts by mass of ε-caprolactone, and 0.5 parts by mass of hydroquinone as a polymerization inhibitor were added to a reaction flask, and the mixture was stirred at 90°C for 5 hours using a mantle heater. Then, 148 parts by mass of phthalic anhydride was added and stirred for another 5 hours. Next, 340 parts by mass of bisphenol A diglycidyl ether was added to the resulting reaction product, and 0.5 parts by mass of triphenylphosphine was further added, and the mixture was stirred at 110°C for 5 hours to obtain a curable resin A. 1 H-NMR and 13 It was confirmed by C-NMR that the curable resin A contains 50% by mass of a compound represented by the following formula (3), 25% by mass of a compound represented by the following formula (4), and 25% by mass of bisphenol A diglycidyl ether (P of the curable resin A). Ecan be considered as 0.5).
[0072] [ka]
[0073] [ka]
[0074] (Preparation of hardening resin B) Curable resin B was obtained in the same manner as in "(Preparation of curable resin A)" above, except that the blending amount of ε-caprolactone was 228 parts by mass. 1 H-NMR and 13 It was confirmed by C-NMR that the curable resin B contains 50% by mass of a compound represented by the following formula (5), 25% by mass of a compound represented by the following formula (6), and 25% by mass of bisphenol A diglycidyl ether (P of the curable resin B). E can be considered as 0.5).
[0075] [ka]
[0076] [ka]
[0077] (Preparation of hardening resin C) Curable resin C was obtained in the same manner as in "(Preparation of curable resin A)" above, except that the blending amount of bisphenol A diglycidyl ether was 170 parts by mass. 1 H-NMR and 13 It was confirmed by C-NMR that the curable resin C was the compound represented by the above formula (4).
[0078] (Preparation of hardening resin D) Curable resin D was obtained in the same manner as in "(Preparation of curable resin A)" above, except that the blended amount of ε-caprolactone was 228 parts by mass and the blended amount of bisphenol A diglycidyl ether was 170 parts by mass. 1 H-NMR and 13 It was confirmed by C-NMR that the curable resin D was the compound represented by the above formula (6).
[0079] (Examples 1 to 13, Comparative Examples 1 to 9) According to the compounding ratios shown in Tables 1 and 2, each material was stirred with a planetary stirrer and then uniformly mixed with a ceramic triple roll to obtain sealants for liquid crystal display elements of Examples 1 to 13 and Comparative Examples 1 to 9. Awatori Mixer (manufactured by Thinky Corporation) was used as the planetary stirrer. The epoxy functional group ratio of the curable resin in each of the obtained sealants for liquid crystal display elements is shown in Tables 1 and 2.
[0080] (Low speed compression shear adhesive strength after photocuring) The obtained sealant for liquid crystal display elements was applied in dots to one of two polyimide substrates measuring 45 mm in length, 25 mm in width, and 0.7 mm in thickness so that the diameter when bonded would be 3 mm. The other polyimide substrate was placed on top of the dotted polyimide substrate with the sealant interposed between them, shifted by 10 mm in the longitudinal direction. Then, a metal halide lamp was used to illuminate the substrate with a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 of ultraviolet light for 30 seconds (accumulated light intensity 3000mJ / cm 2 ) to obtain a test piece having a 5.0 μm thick cured product of the sealant. The metal halide lamp used was SE-1500M (manufactured by Sen Special Light Sources Co., Ltd.), and ultraviolet light was irradiated through a 340 nm cut filter (manufactured by Asahi Spectroscopy Co., Ltd.). The compressive shear adhesive strength (low-speed compressive shear adhesive strength) of the obtained test piece was measured using an autograph AGX (manufactured by Shimadzu Corporation) in accordance with JIS K 6852 at 25°C and a shear rate of 1 mm / sec. The results are shown in Tables 1 and 2.
[0081] (Storage modulus after photocuring) Each of the obtained sealants for liquid crystal display elements was subjected to irradiation with a metal halide lamp at a wavelength of 365 nm and an illumination intensity of 100 mW / cm. 2 of ultraviolet light for 30 seconds (accumulated light intensity 3000mJ / cm 2 ) to obtain a cured product. The metal halide lamp used was an SE-1500M (manufactured by Sen Special Light Sources Co., Ltd.), and ultraviolet light was irradiated through a 340 nm cut filter (manufactured by Asahi Spectroscopy Co., Ltd.). The obtained cured product was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device under the conditions of tensile mode, test piece width 5 mm, thickness 0.35 mm, grip width 25 mm, heating rate 10°C / min, and frequency 5 Hz, and the storage modulus at 25°C was measured. The results are shown in Tables 1 and 2.
[0082] <Evaluation> The sealants for liquid crystal display elements obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 and 2.
[0083] (Adhesion to alignment film) A substrate with an alignment film was produced by spin-coating an imide resin onto a glass substrate with an ITO thin film, pre-baking it at 80°C, and then baking it at 230°C. SE7492 (manufactured by Nissan Chemical Industries, Ltd.) was used as the imide resin. The thickness of the resulting alignment film (imide alignment film) was 100 nm. In 100 parts by mass of each sealant for liquid crystal display elements obtained in the examples and comparative examples, 1 part by mass of silica spacers was uniformly dispersed using a planetary stirrer. SI-H055 (manufactured by Sekisui Chemical Co., Ltd.) was used as the silica spacer. Next, the sealant with the silica spacers dispersed therein was dropped in small droplets onto the alignment film of the substrate with an alignment film. The substrate with the alignment film onto which the sealant had been dropped was then bonded in a cross shape with another substrate with an alignment film via the sealant, and the substrate was illuminated with a metal halide lamp at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 of ultraviolet light for 30 seconds (accumulated light intensity 3000mJ / cm 2) and then heated at 120°C for 1 hour to obtain an adhesive test piece. The metal halide lamp used was SE-1500M (manufactured by Sen Special Light Sources Co., Ltd.), and ultraviolet light was irradiated through a 340 nm cut filter (manufactured by Asahi Spectroscopy Co., Ltd.). The strength at which the panel peeled off occurred was measured when the edge of the substrate in the prepared adhesive test piece was pressed at a speed of 5 mm / min using a metal cylinder with a radius of 5 mm. The adhesiveness to the alignment film was evaluated by dividing the measured value (kgf) by the seal diameter (cm) as follows: 3.0 kgf / cm or more is marked as "◎", 2.5 kgf / cm or more but less than 3.0 kgf / cm is marked as "○", 2.0 kgf / cm or more but less than 2.5 kgf / cm is marked as "△", and less than 2.0 kgf / cm is marked as "×".
[0084] (moisture permeability) Each of the sealing materials for liquid crystal display elements obtained in the Examples and Comparative Examples was applied onto a smooth release film using a coater. Then, the sealing materials were irradiated with a metal halide lamp at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 of ultraviolet light for 30 seconds (accumulated light intensity 3000mJ / cm 2 ), and then heated at 120°C for 1 hour to obtain a 300μm thick film for moisture permeability measurement. SE-1500M (Sen Tokushu Kogen) was used as the metal halide lamp, and ultraviolet light was irradiated through a 340nm cut filter (Asahi Spectroscopy). A moisture permeability test cup was produced according to the method for testing moisture permeability of moisture-proof packaging materials (cup method) of JIS Z 0208, and the obtained moisture permeability measurement film was attached to it. The cup was then placed in a constant temperature and humidity oven at a temperature of 80°C and a humidity of 90%RH to measure the moisture permeability.
[0085] (Anti-peeling properties after photocuring) One part by mass of silica spacer was added to 100 parts by mass of each sealant for liquid crystal display elements obtained in the examples and comparative examples, and the mixture was uniformly dispersed by a planetary stirrer. The mixture was defoamed to remove bubbles in the sealant for liquid crystal display elements, and then filled into a syringe for dispensing, and defoamed again. SI-H055 (manufactured by Sekisui Chemical Co., Ltd.) was used as the silica spacer, and PSY-10E (manufactured by Musashi Engineering Co., Ltd.) was used as the syringe for dispensing. Next, the sealant for liquid crystal display elements was applied to a glass substrate so as to draw a frame using a dispenser. SHOTMASTER300 (manufactured by Musashi Engineering Co., Ltd.) was used as the dispenser. Then, minute droplets of FFS liquid crystal were applied dropwise into the frame of the sealant for liquid crystal display elements using a liquid crystal dropping device. Another glass substrate was placed on the glass substrate on which the FFS liquid crystal had been applied dropwise, with the sealant for liquid crystal display elements interposed therebetween, and the two substrates were bonded together under a reduced pressure of 5 Pa using a vacuum bonding device to obtain a cell. The FFS liquid crystal used was JC-5223XX (manufactured by Chisso Corporation). The resulting cell was illuminated with a metal halide lamp at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 of ultraviolet light for 30 seconds (accumulated light intensity 3000mJ / cm 2 ) was irradiated to produce a liquid crystal display element in which the sealant for liquid crystal display elements was cured by light alone. The metal halide lamp used was SE-1500M (manufactured by Sen Special Light Sources Co., Ltd.), and the ultraviolet light was irradiated through a 340 nm cut filter (manufactured by Asahi Spectroscopic Co., Ltd.). The obtained liquid crystal display element was exposed to an ultrasonic cleaner (manufactured by AS ONE Corporation, "VS-10003", 28kH condition) for 10 minutes. After the exposure, the liquid crystal display element was observed under a microscope, and peeling prevention properties after photocuring were evaluated by rating it as "○" if no peeling of the substrate was observed, and "×" if peeling of the substrate was observed.
[0086] [Table 1]
[0087] [Table 2] [Industrial Applicability]
[0088] According to the present invention, it is possible to provide a sealant for liquid crystal display elements which has excellent adhesion to an alignment film and moisture-proofing properties, and which can suppress peeling after photocuring even when applied to a large substrate.
Claims
1. A sealant for a liquid crystal display element, comprising a curable resin and a photopolymerization initiator, The curable resin contains a compound represented by the following formula (1): 3000mJ / cm of ultraviolet light with a wavelength of 365nm 2 The cured product of the sealant for liquid crystal display elements obtained by irradiating the liquid crystal display element has a thickness of 5.0 μm, and the compressive shear adhesive strength to polyimide measured at 25° C. and a shear rate of 1 mm / sec according to JIS K 6852 is 15 kgf / cm 2 That's all. A sealant for a liquid crystal display device. 【Chemistry 1】 In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a group represented by the following formula (2-1), (2-2), or (2-3), and R 3 represents a methylene group, a methylmethylene group, a dimethylmethylene group, or a sulfonyl group; X represents a lactone ring-open structure; and n is 1 or more and 5 or less. 【Chemistry 2】 In formulas (2-1) to (2-3), * represents a bonding position; in formula (2-2), a is an integer of 1 or more and 8 or less; in formula (2-3), b is an integer of 1 or more and 8 or less; c is an integer of 1 or more and 3 or less; and d is an integer of 1 or more and 8 or less.
2. Further, it contains an organic filler, 2. The sealant for liquid crystal display elements according to claim 1, wherein the content of said organic filler is 5 parts by mass or more based on 100 parts by mass of said curable resin.
3. The ratio of the number of epoxy groups in one molecule of the compound contained in the curable resin to the total number of epoxy groups and (meth)acryloyl groups in the compound molecule is P E When the above formula is used, P in the entire curable resin E 3. The sealant for liquid crystal display elements according to claim 1, wherein the epoxy functional group ratio, expressed as a mass average value, is 30% or more.
4. Further, it contains an inorganic filler, 3. The sealant for liquid crystal display elements according to claim 1, wherein the content of the inorganic filler is 5 parts by mass or more and 30 parts by mass or less based on 100 parts by mass of the curable resin.
5. 3000mJ / cm of ultraviolet light with a wavelength of 365nm 2 After irradiation, the composition is heated at 120°C for 1 hour to obtain a cured product having a thickness of 300 µm. The moisture permeability of the cured product in an environment of 80°C and 90% RH, as measured according to JIS Z 0208, is 75 g / m 2 The sealant for liquid crystal display elements according to claim 1 or 2, wherein the shelf life is 24 hours or less.
6. 3000mJ / cm of ultraviolet light with a wavelength of 365nm 2 3. The sealant for liquid crystal display elements according to claim 1, wherein the storage modulus at 25° C. of the cured product obtained by irradiation is 3.5 GPa or less.
Citation Information
Patent Citations
Sealing agent for dropping process of LCD panel
JP2001133794A
Sealing agent for liquid crystal one-drop-fill method, vertical conducting material and liquid crystal display element
JP2010230713A
Curing resin composition and sealants and end-sealing materials for displays
WO2002092718A1
Curable composition
WO2006009308A1
Sealing material for the liquid crystal dispensing method, transferring material and liquid crystal display devices
WO2006120998A1